Irish cultural politics, Thomas McGreevy and the Avant-Garde, 1922-1941 - Hutton-Williams, FB (2015)
This thesis analyses the responses of Irish writers and painters to a phase of national self-assertion that had arguably lost its liberating potential. It shows how the exhaustion of revolutionary pressures in Ireland after independence complicates the ties between creative activity and political activism. Drawing on a wide range of scholarship within political theory, literary criticism and art history, I chart an emerging network of literary and artistic techniques that confronts the representational aesthetics of the nation with strategies of paradox, reversal and renewal. My readings of the work of Denis Devlin, Samuel Beckett, James Joyce, Mainie Jellett, Jack Butler Yeats and, in particular, Thomas McGreevy, provide a means by which to distinguish other cultural possibilities that were imagined and pursued from 1922 to 1941, including McGreevy’s own aspiration to remould 'A Cultural Irish Republic'. The thesis argues that Ireland's political and artistic avant-garde were forcibly divided during this period: two factions that had been split apart by the effects of civil war and censorship. As such it will be preoccupied with a central question: how to sustain cultural strategies of revolutionary significance when the frontier between creative activity and political activism can no longer be straightforwardly crossed.